2017
DOI: 10.1002/jbt.21917
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphene enhances radiosensitivity of hepatocellular carcinoma through suppression of the NF‐κB pathway

Abstract: Sulforaphene (SFE), a naturally occurring isothiocyanate found in cruciferous vegetables, has attracted increasing attention for its anti-cancer effect in many cancers, including hepatocellular carcinoma (HCC). However, the precise role of SFE in the radiosensitivity of HCC is still unclear. Here, cell proliferation and apoptosis were detected by MTT and flow cytometry assay, respectively. The activity of NF-κB was further evaluated by ELISA. We also observed the effect of SFE and/or radiation on tumor growth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The response to curcumin was associated with the inhibition of NF-κB and downstream signaling such as MYC, JNK, Cyclin D1, and STAT3 [80]. Curcumin, as well as sulforaphane, a naturally occurring isothiocyanate found in cruciferous vegetables, has been shown to further sensitize human hepatocellular carcinoma cells to radiation through inhibition of radiation-induced NF-κB activity [104,105]. Besides natural compounds, NF-κB inhibitors have also been developed and tested in pre-clinical models.…”
Section: Nf-κb As a Target For Cancer Prevention And Therapymentioning
confidence: 99%
“…The response to curcumin was associated with the inhibition of NF-κB and downstream signaling such as MYC, JNK, Cyclin D1, and STAT3 [80]. Curcumin, as well as sulforaphane, a naturally occurring isothiocyanate found in cruciferous vegetables, has been shown to further sensitize human hepatocellular carcinoma cells to radiation through inhibition of radiation-induced NF-κB activity [104,105]. Besides natural compounds, NF-κB inhibitors have also been developed and tested in pre-clinical models.…”
Section: Nf-κb As a Target For Cancer Prevention And Therapymentioning
confidence: 99%
“…Besides the MAPK signaling pathway, other pathways and mechanisms mediate the occurrence and development of multiple types of tumors induced by sulforaphene. An increasing number of studies have demonstrated that sulforaphene promotes tumorigenesis and metastasis through the regulation of cell proliferation, migration, invasion, and apoptosis [21]. Recently, sulforaphene was reported to inhibit tumor growth in colon cancer through the induction of glutathione ablation and microtubule depolymerization [26].…”
Section: Discussionmentioning
confidence: 99%
“…Ren et al found that radiation increased NF‐κB activity, while NF‐κB inhibitor enhanced radiation‐induced cell death. Blocking the NF‐κB pathway sensitized the radiosensitivity of HCC cells . NF‐κB in the irradiated cells determined radioresistance of the tumor cells .…”
Section: Discussionmentioning
confidence: 99%